Adjusting Labor along the Intensive MarginS - Jeff E. Biddle; Daniel S. Hamermesh (Institute of Labor Economics (IZA), 2024)
We expand the analysis of cyclical changes in labor demand by decomposing changes along the intensive margin into those in days/week and in hours/day. Using large cross sections of U.S. data, 1985-2018, we observe around of the adjustment in weekly hours occurring through changing days/week. There is no adjustment of days/week in manufacturing; but 1/3 of the adjustment outside manufacturing occurs through days/week. The desirability of bunched leisure implies that secular shifts away from manufacturing have contributed to increasing economic welfare.
Keywords: J23; E24; J21; 330; days; labor demand; work hours; recessions